Business battles in the US energy sector : lessons for a clean energy transition - Downie, Christian (Abingdon, Oxon ; New York, NY : Routledge, 2019)
This book is ground breaking in its study of business actors in climate and energy politics. While various studies have demonstrated the influence of business actors across multiple policy domains, this is the first to examine the behaviour of business actors in energy centricindustries in the US that will be vital for achieving a clean energy transition, namely the oil, gas, coal, utility, and renewable industries. Drawing on almost 80 interviews with senior energy executives, lobbyists, and policymakers, it asks two central questions: (i) how and why are business actors shaping energy policy contests in the US? And (ii) what are the implications for policymakers? In answering these questions, this book provides new insights about the preferences and strategies of business in the energy sector, and, significantly, it identifies strategies for policymakers seeking to regulate energy in the face of political resistance from incumbent fossil fuel industries. This book will be of particular value to students, scholars, and policymakers working in the fields of energy, climate, and environmental politics, as well as individuals generally interested in the role that business exerts over policy processes.
Introduction -- Understanding business preferences, strategies and influence -- Exporting to the world: policy contests in the oil and gas industries -- The war on coal: policy contests in the coal and utility industries -- The rise of renewable power: policy contests in the wind and solar industries -- Re-thinking business behaviour in the us energy sector -- What should policymakers do?
OCLC-licensed vendor bibliographic record.
Keywords: Energy industries -- Environmental aspects -- United States; Energy development -- Environmental aspects -- United States; Energy policy -- Environmental aspects -- United States; BUSINESS & ECONOMICS / Real Estate / General; BUSINESS & ECONOMICS / Industries / Energy Industries; BUSINESS & ECONOMICS / Development / Sustainable Development; BUSINESS & ECONOMICS / Government & Business